Pengaruh gadget terhadap prestasi belajar mahasiswa Universitas Islam Negeri Maulana Malik Ibrahim Malang - Prasetyo, Prayogi (Maliki Interdisciplinary Journal, 2024)
The This research aims to investigate the impact of using gadgets on the learning achievement of students who tend to be addicted. Thus, the main aim of this research is to understand how some students are addicted to devices, which can affect students’ academic performance. The method used in this research is a quantitative research method through data collection. The results of this research conclude that gadgets are within the scope of students. The use of electronic devices has both good and bad effects on academic achievement. One of the positive impacts is that students use these devices as learning tools. However, the negative impacts include changes in students’ personalities, becoming less socially active, device addiction, and lack of motivation in studying. These bad impacts tend to be more dominant than the positive impacts. Based on research, the use of these devices is believed to cause a decrease in learning achievement. This study is a reflection for students to utilize electronic devices for important purposes in learning to increase academic achievement